2022
DOI: 10.1111/jch.14581
|View full text |Cite
|
Sign up to set email alerts
|

Association of three insulin resistance indices with hypertension and body weight among Uyghur adults in rural areas of Xinjiang, China

Abstract: Obesity and insulin resistance are significant contributors to hypertension. There is a high prevalence of obesity among Uyghurs in the rural areas of Xinjiang, China. Therefore, this study aimed to explore the association between insulin resistance indices and hypertension according to different body weights in rural Uyghur residents of Xinjiang, China. A total of 12 813 local Uyghur residents were recruited for the study. Excluding those with incomplete data and those using antihypertensive, lipid-lowering, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…4b, p for subgroup difference all > 0.05). Results of meta-analysis with METS-IR analyzed in continuous variables also showed that METS-IR was associated with the risk of hypertension (four datasets [26][27][28], RR for 1-unit increment of METS-IR: 1.15, 95 % CI: 1.08 to 1.23, p < 0.001, I 2 = 79 %; ▶ Fig. 5).…”
Section: Meta-analysis Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…4b, p for subgroup difference all > 0.05). Results of meta-analysis with METS-IR analyzed in continuous variables also showed that METS-IR was associated with the risk of hypertension (four datasets [26][27][28], RR for 1-unit increment of METS-IR: 1.15, 95 % CI: 1.08 to 1.23, p < 0.001, I 2 = 79 %; ▶ Fig. 5).…”
Section: Meta-analysis Resultsmentioning
confidence: 74%
“…As shown in Table 1 , eight observational studies, including two cohort studies 21 28 and six cross-sectional studies 22 23 24 25 26 27 , were included in the meta-analysis. These studies were published between 2019 and 2022, and performed in Mexico 21 , China 22 23 24 25 , 27 28 , and Japan 26 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations